Utilization of hemihydrate phosphogypsum for the preparation of porous sound absorbing material. (20th February 2020) - Ma, Baoguo; Jin, Zihao; Su, Ying; Lu, Wenda; Qi, Huahui; Hu, Penghui
Graphical abstract: Highlights: β-HPG was used for the preparation of PSAM to achieved the effective utilization of PG. Pore-forming agent and basalt fiber were used to form interconnected pores in PSAM. High efficiency sound absorbing material can be prepared with composite structure. Abstract: Phosphogypsum (PG) as an industrial by-product of phosphoric acid production causes severe environmental pollution. Beta-hemihydrate phosphogyspum (β-HPG) obtained by low temperature calcination of PG can be used for the preparation of functional building materials to achieve its utilization. This work aims to utilize β-HPG as raw material for the preparation of porous sound absorbing material (PSAM). The effects of pore-forming agent, basalt fiber and expanded perlite on the properties of PSAM were investigated systematically by the analyses of sound absorption coefficient, mechanical strength, bulk density, open porosity and microstructure. In addition, the sound absorption properties of PSAM were evaluated by noise reduction coefficient in accordance with the corresponding Chinese standard. The results show that pore-forming agent and basalt fiber can form a large number of interconnected pores in the PSAM, and expanded perlite can further increase the sound absorption properties of PSAM by the combination of interconnected pore structure and cavity resonance sound absorption structure. High efficiency sound absorbing material can be prepared with 0.6 wt% pore-forming agent, 1 wt% basalt fiber and 6 wt% expanded perlite by the weight of β-HPG. This work provides an effective and high value-added way for the utilization of PG.